A cross‐sectional pilot study to estimate the prevalence of and risk factors for leptospirosis in South‐Western Victorian dairy herds, 2017. Issue 9 (20th July 2020) - Erregger, E; Stevenson, MA; Beggs, DS; Oswin, S; Jagoe, SP; Mansell, PD; Pyman, MF
Abstract : Leptospirosis is a zoonosis, found worldwide, affecting many species of animals. We conducted a cross‐sectional study to estimate the prevalence of Leptospira borgpetersenii sv Hardjo and Leptospira interrogans sv Pomona in cattle in dairy herds in South‐Western Victoria, Australia. Fifty‐three herds were enrolled in the study. Urine samples were collected from 15 late‐lactation cows in each herd. A questionnaire was provided to herd managers at the time of each herd visit, asking them to describe the methods they used for controlling leptospirosis, including vaccination. Urine samples were pooled at the herd level and tested for leptospira spp. using real time PCR. Urine samples from individual cows within the positive pooled samples were then tested for Leptospira Hardjo and Leptospira Pomona using qPCR. Four of the 53 herds showed positive leptospirosis results giving an apparent prevalence of 8 (95% CI 2–18) leptospira‐positive herds per 100 herds at risk. Based on the 53 completed questionnaires, leptospirosis vaccination programs were not compliant with label directions in 36 of the 52 vaccinated herds: 69 (95% CI 55–81) of 100 herd managers that routinely vaccinated for leptospirosis did not comply with label directions. One herd was completely unvaccinated. Based on our findings, we estimate that approximately 10% of dairy farms in South‐Western Victoria are likely to be infected with leptospirosis. While most herds are vaccinating for leptospirosis, most are not doing so according to label directions. We conclude that herd managers need to be better educated regarding leptospirosis vaccination programs.